Positive Mood and the Perception of Variability Within and Between Groups - Stroessner, Steven J.; Mackie, Diane M.; Michalsen, Venezia (Group Processes & Intergroup Relations, 2005)
Three experiments investigated the effects of positive mood on perceptions of variability within and between groups. Participants formed impressions of two different and highly variable groups under a neutral or positive mood. When participants expected to learn about both groups, positive mood increased perceived intergroup similarity but did not affect perceived intragroup variability. In contrast, when participants expected to learn about only one group, judgments of intergroup and intragroup similarity were both affected by mood. Mood and the intergroup context influenced the nature and degree of information processing and resultant judgments of variability in social groups.
Keywords: dept.soc; peer-reviewed

Are Suicide Attempters Who Self-Mutilate a Unique Population? - Stanley, Barbara; Gameroff, Marc J.; Michalsen, Venezia; Mann, J. John (American Journal of Psychiatry, 2001)
OBJECTIVE: Individuals who mutilate themselves are at greater risk for suicidal behavior. Clinically, however, there is a perception that the suicide attempts of self-mutilators are motivated by the desire for attention rather than by a genuine wish to die. The purpose of this study was to determine differences between suicide attempters with and without a history of self-mutilation. METHOD: The authors examined demographic characteristics, psychopathology, objective and perceived lethality of suicide attempts, and perceptions of their suicidal behavior in 30 suicide attempters with cluster B personality disorders who had a history of self-mutilation and a matched group of 23 suicide attempters with cluster B personality disorders who had no history of self-mutilation. RESULTS: The two groups did not differ in the objective lethality of their attempts, but their perceptions of the attempts differed. Self-mutilators perceived their suicide attempts as less lethal, with a greater likelihood of rescue and with less certainty of death. In addition, suicide attempters with a history of self-mutilation had significantly higher levels of depression, hopelessness, aggression, anxiety, impulsivity, and suicide ideation. They exhibited more behaviors consistent with borderline personality disorder and were more likely to have a history of childhood abuse. Self-mutilators had more persistent suicide ideation, and their pattern for suicide was similar to their pattern for self-mutilation, which was characterized by chronic urges to injure themselves. CONCLUSIONS: Suicide attempters with cluster B personality disorders who have a history of self-mutilation tend to be more depressed, anxious, and impulsive, and they also tend to underestimate the lethality of their suicide attempts. Therefore, clinicians may be unintentionally misled in assessing the suicide risk of self-mutilators as less serious than it is.
Keywords: dept.soc; peer-reviewed

Exploring the Links Between Student Learning and Instructor/Course Evaluation. - Polka, Joseph A. (2006)
Keywords: dept.soc; faculty_collection; sabbatical_report

Race, Ethnicity, and the American Urban Mainstream - Doob, Christopher Bates (Pearson/Allyn and Bacon, 2005)
"Race, Ethnicity, and the American Urban Mainstream uses history, biography, and sociological analysis to examine the achievements and struggles of racial and ethnic groups in American cities. This text is organized around social systems (politics, housing, education, economics, and work) rather than groups or concepts such as prejudice and discrimination. A group of in-depth profiles of minority communities, in cities such as Oakland, Detroit, Los Angeles, and Chicago, help to illustrate major concepts."–BOOK JACKET.
Keywords: Canada; United States; Ethnic relations; Ethnic relations; United States; Race relations; United States; Social conditions; Canada; Social conditions; Racism; United States; United States; City and town life; United States; Cultural pluralism; Urban minorities; dept.soc; faculty_collection

Murder by Design - Bloch, Jon P. (St. Martin's Minotaur, 2004)
Opting to have his home remodeled on a popular cable reality show, celebrity gossip columnist Rick Domino is horrified when the consulting designer is found brutally murdered, a case for which Rick teams up with unstylish but attractive police detective Terry Zane.
Keywords: Crimes against; Fiction; Fiction; Hollywood (Los Angeles; Calif.); Fiction; Interior decorators; Fiction; Television programs; Gossip columnists; dept.soc; faculty_collection

Justice for the Poor: A Study of Criminal Defense Work - Emmelman, Debra S. (Ashgate, 2003)
Keywords: Public defenders; United States; United States; Criminal justice; Administration of; United States; Legal assistance to the poor; United States; Plea bargaining; dept.soc; faculty_collection

Best Murder of the Year - Bloch, Jon P. (St. Martin's Minotaur, 2002)
Gossip columnist Rick Domino is stunned when his lover, actor Shane Kirk, wins an Oscar for Best Actor but is nowhere to be found, and when Rick finally finds Shane, who is holding a gun and a dead body, Shane takes off, leaving Rick to face the police.
Keywords: Academy Awards (Motion pictures); Fiction; Fiction; Gay men; Fiction; Gossip columnists; Fiction; Hollywood (Los Angeles; Calif.); Fiction; Motion picture industry; dept.soc; faculty_collection

An Ethnographic Study of an American Conservative Synagogue - Laskin, Martin (E. Mellen Press, 2002)
Keywords: Connecticut; Hamden; History; Liturgy; Jews; Sociological aspects; Conservative Judaism; Temple Beth Shalom (Hamden; Conn.); Synagogues; dept.soc; faculty_collection

Finding Your Leading Man: How to Create Male-to-Male Intimacy and Make Your Relationship a Blockbuster - Bloch, Jon P. (St. Martin's Griffin, 2000)
Keywords: Gay men; Interpersonal relations; Intimacy (Psychology); dept.soc; faculty_collection

Sociology: An Introduction - Doob, Christopher Bates; Faupel, Charles E. (Harcourt Press, 2000)
Keywords: Sociology; dept.soc; faculty_collection

Justice for the Poor: A Case Study of Criminal Defense Work. - Emmelman, Debra S. (Fall; Sociology/Anthropology., 2000)
Keywords: dept.soc

Book Review: Superpredators: The Demonization of Our Children by the Law, by Peter Elikann, Perseus Publishing, 1999. - Kenty, Jessica L. (Bimonthly Review of Law Books, 2000)
Keywords: book.review; dept.soc; ⛔ No DOI found

Early Isolation: Racial and Economic Segregation in U.S. Public Elementary Schools - Kenty-Drane, Jessica L. (Race, Gender & Class, 2009)
The literature shows that racially and economically segregated schools diminish educational outcomes for students in non white schools with impoverished peers (Frankenberg & Lee, 2002; Mayer, 2000). To reveal which children are apt to begin their education in high minority and poor schools, this study drew on nationally representative data from the Early Childhood Longitudinal Study. Evidence documents variations in school racial and economic contexts according to children's race and social class backgrounds. Over half of Black and Hispanic first-graders attend segregated minority and poor schools while very few White first-graders do so. Additional analyses reveal that while social class is a useful predictor of educational segregation, it is less predictive for Black and Asian students than for White and Hispanic students.
Keywords: dept.soc; ⛔ No DOI found

The racial wealth gap - Shapiro, Thomas M.; Kenty-Drane, Jessica L. (African Americans in the U.S. Economy, 2005)
Over the last several decades, academic discourse on racial inequality has focused primarily on political and social issues with significantly less attention on the complex interplay between race and economics. African Americans in the U.S. Economy represents a contribution to recent scholarship that seeks to lessen this imbalance. This book builds upon, and significantly extends, the principles, terminology, and methods of standard economics and black political economy. Influenced by path-breaking studies presented in several scholarly economic journals, this volume is designed to provide a political-economic analysis of the past and present economic status of African Americans. The chapters in this volume represent the work of some of the nation's most distinguished scholars on the various topics presented. The individual chapters cover several well-defined areas, including black employment and unemployment, labor market discrimination, black entrepreneurship, racial economic inequality, urban revitalization, and black economic development. The book is written in a style free of the technical jargon that characterizes most economics textbooks. While the book is methodologically sophisticated, it is accessible to a wide range of students and the general public and will appeal to academicians and practitioners alike.
Google-Books-ID: itUWFxWk4OYC
Keywords: Social Science / Ethnic Studies / African American Studies; dept.soc

Juvenile delinquency - Kenty-Drane, Jessica L. (Men and masculinities: a social, cultural, and historical encyclopedia, 2004)
This reference analyzes, summarizes, and explains the complexities of men's lives and the idea of modern manhood. It looks at literature, art, and music from a gender perspective, and covers intimacy, sexual violence, pornography, sexism and rituals.
OCLC: 301173623
Keywords: dept.soc

Stylistic sabotage and Thorstein Veblen's scientific irony - Cassano, G. (Journal of Economic Issues, 2005)
4 citations (Crossref) [2023-10-31]
Keywords: dept.soc

Book Review: corrections: A comprehensive view - Ryan, Michael (Criminal Justice Review, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/162-405-532-876-178 tex.type: [object Object]
Keywords: book.review; dept.soc

The new and improved clint eastwood: change and persistence in promise keepers self-help literature - Bloch, Jon P (Sociology of Religion, 2000)
Like other expressions of Christian conservatism, the Promise Keepers (PK) often enact complex and strained relationships between social change and social persistence. These strains are evident in the official PK literature, which employs techniques not unlike those used by mainstream pop psychology. These include the use of “scientific”-like classifications of information, authors presented as “experts” on the topic at hand, and the use of exercises to be enacted individually or in small PK discussion groups. Collectively, these strategies suggest that conservative Christians deal with many of the same complex role demands as non-conservatives. In Particular, the PK stance on gender roles, though Promoted as unambiguously “traditional” in favoring male leadership and female submission, in actuality often reflects acknowledgment and perhaps acceptance of some of the more egalitarian changes in gender role norms. Sociological implications and directions for future research are discussed.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-278-825-342-722 tex.type: [object Object]
Keywords: dept.ant; dept.soc

Identifying the involvement of multiple carnivore taxa with archaeological bone assemblages - Selvaggio, Marie M; Wilder, Joseph (Journal of Archaeological Science, 2001)
Information on the number of carnivore taxa that were involved with archaeological bone assemblages is pertinent to questions of site formation, hominid and carnivore competition for carcasses and the sequence of hominid and carnivore activity at sites. A majority of early archaeological bone assemblages bear evidence that both hominids and carnivores removed flesh and/or marrow from the bones. Whether flesh specialists (felids) or bone-crunchers (hyaenas), or both, fed upon the carcasses is crucial for deciphering the timing of hominid involvement with the assemblages. Here we present an initial attempt to differentiate the tooth mark signature inflicted on bones by a single carnivore species versus multiple carnivore taxa. Quantitative data on carnivore tooth pits, those resembling a tooth crown or a cusp, are presented for two characteristics: the area of the marks in millimetres, and the shape as determined by the ratio of the major axis to the minor axis of the mark. Tooth pits from bones modified by extant East African carnivores and latex impressions of tooth pits from extinct carnivore species are compared to those in the FLK Zinjanthropus bone assemblage. Data on tooth mark shape indicate greater variability in the Zinj sample than is exhibited by any individual extant or extinct carnivore species in the comparative sample. Data on tooth mark area demonstrate that bone density is related to the size of marks. Taken together, these data support the inference that felids defleshed bones in the Zinj assemblage and that hyaenas had final access to any grease or tissues that remained. © 2001 Academic Press.
165 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-668-240-742-014 tex.type: [object Object]
Keywords: Carnivore tooth marks; Methodology; Site formation; Taphonomy; carnivore; dept.ant; dept.soc; feeding; taphonomy; tooth

Violence in the city of women: police and batterers in bahia, brazil - Jackson, Shirley A. (American Journal of Sociology, 2009)
0 citations (Crossref) [2023-10-31] tex.eissn: 1537-5390 tex.unique-id: ISI:000265676200032
Keywords: dept.soc; peer-reviewed

A whisper toward peace: A theoretical analysis of the council for a parliament of the world religions - Bloch, Jon P (Journal for the Scientific Study of Religion, 2008)
The Council for a Parliament of the World Religions has been meeting since 1993 to foster a global religious ethic toward world peace, based on the premise that major world religions share this ethic in common. Roland Robertson's multidimensional model of globalization is utilized to analyze the Parliament's foundational Declaration, and explore why the Parliament's message is not receiving wider attention. Excerpts from anti-Parliament sources are included. Based on this analysis, the Parliament appears to have a limited conception of globalization, and so offers but a partial knowledge claim on how religion can resolve global problems. Seen in this light, it is not surprising that some oppose the Parliament's agenda, feel alienated by it, or-given its limitations-are not aware of it.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/050-703-232-358-605 tex.type: [object Object]
Keywords: dept.soc

Book Review: The path of the devil: early modern witch hunts. by gary jensen. her hidden children: the rise of wicca and paganism in america. by chas s. clifton. new age and neopagan religions in america. by sarah m. pike. witchcraft and magic: contemporary north america. edited by helen a. berger. voices from the pagan census: a national survey of witches and neo-pagans in the united states. by helen a. berger, evan a. leach, and leigh s. shaffer. researching paganisms (the pagan studies series). edited by jenny balin, douglass ezzy, and graham harvey - Bloch, Jon P. (Journal for the Scientific Study of Religion, 2008)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-902-592-460-172
Keywords: book.review; dept.soc

Cyber wars: Catholics for a free choice and the online abortion debate - Bloch, Jon P. (Review of Religious Research, 2007)
Catholics for a Free Choice (CFFC) performs considerable advocacy online, through its website as well as through press releases and interviews that appear at other sites. Opponents to CFFC also frequently post online. This article analyzes this online debate to explore how it is conceptually framed. CFFC presents a discourse that is promoted as finding ideological consistency between Catholic values and being prochoice, and which addresses a greater social good beyond the Church per se. In making these self-referential claims, CFFC could be viewed as a “community of discourse” (Wuthnow 1989) that reckons with “problems of articulation” by dealing with both specific and broader tensions. Online opponents to CFFC likewise could be viewed as communities of discourse that promote themselves as having the true Catholic values that serve the greater good. On balance, CFFC online would seem to reflect the larger quandaries of abortion discourse, whereby the Internet can offer a representative depiction of democratic free speech articulated on this controversial issue. Yet at the same time, there is little evidence to date that this online debate is changing anyone's mind or building a new consensus, despite some efforts on the part of CFFC to do so.
tex.unique-id: ISI:000252110700004
Keywords: dept.soc; ⛔ No DOI found